TikTok Meets TBLT: Student Perspectives on Social Media?Integrated Task?Based Speaking Challenges in Advanced EFL Learning - Nisa, Nadia Khairun; Irmayani, Irmayani (English Language Education Program, Faculty of Education and Teacher Training, Sulthan Thaha Saifuddin State Islamic University of Jambi, 2025)
This study explores advanced EFL (English as a Foreign Language) learners' perceptions of using TikTok within Task-Based Language Teaching (TBLT) in a speaking task context. TBLT is an approach to language teaching that enables learners to communicate in the real world via meaningful tasks; TikTok is a perfect platform for creating authentic content and engaging in meaningful tasks. This study employed a mixed-methods data collection approach and obtained data from 85 undergraduate English major students from a university in Indonesia. The data collection instruments included structured questionnaires in which students rated Likert-scale items and offered follow-up semi-structured interviews. The participants completed speaking activities where they created TikTok videos related to storytelling, discussion, and instructional content using the English language.Quantitative data were analyzed using descriptive statistics and qualitative data responses were coded using thematic analysis. The findings indicated that TBLT tasks that utilized TikTok increased student engagement, provided opportunities to develop speaking confidence and fluency as students were given repeating opportunities to see and perform, and, as well, students appreciated the flexibility to be creative, the multimodal nature of the content (audio, video, caption), the ability to re-watch and self-reflect their speaking performance, and reduced speaking anxiety. The students described that TikTok's format being asynchronous, and not requiring real-time oral performance allowed them to operate in a lower pressure environment associated with real-time events.